2015
DOI: 10.5539/elt.v8n10p30
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Using a Web-Based Approach to Teach Reading Strategies to Iranian EFL Learners

Abstract: Applying new technologies with their effective potentials have changed education and, consequently, the L2 teacher role. Coping with online materials imposes the necessity of employing Web-based approaches in L2 instruction. The ability to use reading strategies in a Web-based condition needs sufficient skill which will be fulfilled if it is integrated in pedagogy. The main focus of the present study was to investigate the efficiency of teaching reading strategies in a Web-based condition to Iranian EFL learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The study's results also were consistent with other findings in the literature, including those of Kilickaya andKrajka (2010), Huang (2013), and Dehghanpour and Hashemian (2015). Specifically, the current study and these studies together confirmed the advantages that online reading environments offer to L2 reading instructions including engaging learners in interactive reading activities, engaging interest by using multiple modalities (text, video, pictures, sound, animations, reader control over paths followed in completing assignments, and different levels of support and comprehension assistance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study's results also were consistent with other findings in the literature, including those of Kilickaya andKrajka (2010), Huang (2013), and Dehghanpour and Hashemian (2015). Specifically, the current study and these studies together confirmed the advantages that online reading environments offer to L2 reading instructions including engaging learners in interactive reading activities, engaging interest by using multiple modalities (text, video, pictures, sound, animations, reader control over paths followed in completing assignments, and different levels of support and comprehension assistance.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, Dehghanpour and Hashemian (2015) examined the efficiency of teaching reading strategies in a Web-based setting to 30 Iranian EFL learners. Participants learned four general reading strategies, which were practiced through three stages of cognitive theory: cognitive, associative, and autonomous.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%
“…They also claimed that web-based lessons can facilitate students 'reading comprehension ability and strategy use, and they can apply the reading strategies explicitly during the course. The results were consistent to the past studies ( [7]- [10])…”
supporting
confidence: 83%
“…Research studies using web-based instruction to teach reading skills, especially in graduate level, has been found less [7]. Therefore, this study employed web-based lessons to develop Thai graduate students as previous studies showed that web-based instruction is very helpful to assist students' reading skills [7]- [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation